In situ protocol for the determination of dose-response effect of low-fluoride dentifrices on enamel remineralization - Rebeca Lima AFONSO; Juliano Pelim PESSAN; Bruna Babler IGREJA; Camila Fernandes CANTAGALLO; Marcelle DANELON; Alberto Carlos Botazzo DELBEM (University of São Paulo, 2013)
No in situ protocol has assessed the dose-response effects of fluoride dentifrices involving low-fluoride formulations. Objective: To assess the ability of an in situ remineralization model in determining dose-response effects of dentifrices containing low fluoride concentrations ([F]) on bovine enamel. Material and Methods: Volunteers wore palatal appliances containing demineralized enamel blocks and brushed their teeth and devices with the dentifrices supplied (double-blind, crossover protocol) separately for 3 and 7 days. Surface hardness (SH), integrated subsurface hardness (ΔKHN) and [F] in enamel were determined. Data were analyzed by ANOVA, Tukey's test and Pearson's correlation (p<0.05). Results: Dose-response relationships were verified between [F] in dentifrices and SH, ΔKHN and enamel [F]. Higher correlation coefficients between enamel [F] and SH and ΔKHN were obtained for the 3-day period. Significant differences in SH and ΔKHN were observed among all groups for the 3-day period, but not between 0-275, 275-550, and 550-1,100 µg F/g dentifrices for the 7-day period, nor between 3- and 7-day periods for the 1,100 µg F/g groups. Conclusions: Considering that the peak remineralization capacity of the conventional dentifrice (1,100 µg F/g) was achieved in 3 days, this experimental period could be used in future studies assessing new dentifrice formulations, especially at low-fluoride concentrations.